Simulating a Transition to Autonomous Mobility - Caulfield, Brian (My University, 2021)
This study examined the transition from Traditional Vehicles (TVs) to Autonomous Vehicles (AVs) using microsimulation modelling approaches. For this purpose, the study first optimised the parameters of human driving behaviours to find out what would happen if AVs could drive with modified human behaviours. Then, the study acquired the optimised driving behaviours to evaluate how efficient AVs can be within the context of the anticipated driving behaviours. The shared road of AVs and TVs was tested for where the proportion of the AVs incremented by 10% from an entirely traditional network to a network fully occupied by AVs. Such an assessment of the shared road represented the transition periods between TVs and AVs in highway transport. Overall, the simulation results in this study indicated that AVs could substantially improve the quality of traffic, especially by reducing the number of stops, queue length, and delay time. The study also found that TVs and AVs can efficiently share their road, and the improvement in the quality of traffic increases with an increase in the proportion of AVs to TVs, up to a specific level, on the road. In this regard, according to the results from the peak and normal traffic conditions, a road with a 60% share of AVs can see its traffic quality improved as much as a road entirely populated by AVs. Therefore, dedicating 100% of the road traffic to AVs or devoting a dedicated lane for AVs in peak traffic hours might be as efficient as a shared road with 60% AVs.
PUBLISHED
Keywords: Autonomous Vehicles (AV); Traffic simulation; Traffic Modelling; Smart & Sustainable Planet; Transport